Employee Performance Reviewed From Workload, Organizational Culture, Work Experience and Village Office Competence in Kwadungan District, Ngawi - Gulit Danan Prasetyo Utomo; Istiatin Istiatin; Sudarwati Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine and explain the influence of workload, organizational culture, work experience, and competence on the performance of village officials in Kwadungan District, Ngawi. The population of this study was 102 village officials in Kwadungan District, Ngawi, and a sample of 50 people using total sampling technique. Data collection used a questionnaire. Data analysis used Multiple Linear Analysis. The results showed that workload, organizational culture, work experience, and competence contributed 70.5% to performance, while the remaining 29.5% was explained by other variables not included in this study. Suggestions from this research, village officials in Kwadungan District, Ngawi can improve organizational culture and competence and leaders are able to manage employee workloads so that work experience increases to achieve maximum performance results in villages in Kwadungan District, Ngawi.